Pison dominimenke, a new crabronid wasp in Dominican amber (Hymenoptera: Crabronidae). - Bennett, Daniel J.; Engel, Michael S. (Contributions to Entomology = Beiträge zur Entomologie, 2008)
A new crabronid wasp species, Pison menkei sp. n., is described and figured from a single female preserved in Early Miocene (Burdigalian) Dominican amber. The fossil is herein distinguished from extant and extinct congeners and regarded as an isolated species removed from modern Neotropical species groups. It is the seventh named fossil Pison and the second from Dominican amber. Keywords Fossil, paleontology, taxonomy, Tertiary, Miocene, Apoidea. Nomenclatural Acts menkei Bennett & Engel, 2008 (Pison), spec. n.